2021
DOI: 10.1111/1346-8138.15970
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, phase II study on the safety and efficacy of negative pressure closure for the stabilization of split‐thickness skin graft in large or muscle‐exposing defects: The NPSG study

Abstract: Several studies have demonstrated the usefulness of negative pressure closure (NPC) for the stabilization of skin grafts because it provides a uniform pressure to the graft.The results of our previous retrospective study also suggested the superiority of NPC over tie-over methods for the stabilization of split-thickness skin graft (STSG) in large or muscle-exposing defects. However, the usefulness of NPC for graft stabilization is yet to be fully established. This prospective, phase II clinical study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Ito et al 9) reported cases of over-compression even at 100 mmHg and recommended that 50-75 mmHg was appropriate for skin graft fixation. A prospective study on skin graft fixation in STSG by Nakayama et al 10) reported that 50 mmHg might be suitable to prevent adverse effects, such as pain while using the NPWT device. Others have reported that approximately 50 mmHg is sufficient 11) , while 100-125 mmHg is recommended with an emphasis on fixed stability 12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ito et al 9) reported cases of over-compression even at 100 mmHg and recommended that 50-75 mmHg was appropriate for skin graft fixation. A prospective study on skin graft fixation in STSG by Nakayama et al 10) reported that 50 mmHg might be suitable to prevent adverse effects, such as pain while using the NPWT device. Others have reported that approximately 50 mmHg is sufficient 11) , while 100-125 mmHg is recommended with an emphasis on fixed stability 12) .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the strength of negative pressure during fixation has been mentioned in several studies [9][10][11][12] , but none is currently based on a high level of evidence. Therefore, in actual practice, the setting of negative pressure strength is at the clinician's discretion.…”
Section: Introductionmentioning
confidence: 99%
“…5 The use of NPWT for skin graft fixation is advantageous because it provides uniform pressure to the skin graft even when there are large defects or moving parts. 13 There are also reports that the use of NPWT eliminates the need for splints for skin grafts involving the joints of the upper limbs. 14 Reports on suction pressure range from −25 to −125 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NPC showed a tendency toward a shorter time from the harvesting of the skin graft to the end of the NPC graft stabilization than that of the tie-over method. Then, we also conducted a prospective, phase-II clinical study to investigate the safety and efficacy of NPC for the stabilization of STSG in large (longest diameter, >10 cm) or muscle-exposing defects [ 147 ]. In that study, the mean survival rate of the skin graft was higher than 95% at day 10, and the mean time from harvesting of the skin graft to the end of NPC graft stabilization was shorter than 20 min, suggesting that NPC for stabilization of STSG leads not only to a high survival rate of the skin graft but also to a short operative time.…”
Section: Methods For Skin Graftsmentioning
confidence: 99%